2013
DOI: 10.1002/jgra.50352
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in solar quiet (Sq) geomagnetic variations related to Earth's magnetic field secular variation

Abstract: The daily amplitude of the solar quiet (Sq) magnetic variation of the horizontal intensity, H, of observatories at low and midlatitudes is analyzed, in search of significant long‐term trends. These trends are expected based on secular variations of the Earth's magnetic field (B) and increasing concentrations of greenhouse gases which can affect Sq for instance through their effect on ionospheric conductivities and E‐region electron concentration. The hourly horizontal geomagnetic field component, H, measured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…However, the observed long-term trends in the residual Sq amplitudes were greater than those expected from the conductivity changes; thus, other contributions such as CO 2 might also play a role. de Haro Barbas et al (2013) compared these trends with the results obtained from the CMIT model, confirming the role of the secular variation of the geomagnetic field in the long-term changes in Sq. In contrast to these results, Jarvis (2005) found a longterm decrease in the diurnal and semidiurnal spectral power at Lerwick (61.1°N, 358.8°E), Niemegk (52.1°N, 12.7°E), and Tucson (32.2°N, 249.3°E) after removal of solar activity and geomagnetic activity effects.…”
Section: Long-term Variationsupporting
confidence: 59%
See 1 more Smart Citation
“…However, the observed long-term trends in the residual Sq amplitudes were greater than those expected from the conductivity changes; thus, other contributions such as CO 2 might also play a role. de Haro Barbas et al (2013) compared these trends with the results obtained from the CMIT model, confirming the role of the secular variation of the geomagnetic field in the long-term changes in Sq. In contrast to these results, Jarvis (2005) found a longterm decrease in the diurnal and semidiurnal spectral power at Lerwick (61.1°N, 358.8°E), Niemegk (52.1°N, 12.7°E), and Tucson (32.2°N, 249.3°E) after removal of solar activity and geomagnetic activity effects.…”
Section: Long-term Variationsupporting
confidence: 59%
“…Shinbori et al (2014) also found negative trends in the residual Sq amplitude (∼ 10 −4 nT per day) at many stations worldwide. Both Jarvis (2005) and Shinbori et al (2014) used the H -component geomagnetic field, the same as Elias et al (2010) and de Haro Barbas et al (2013). The discrepancies in the long-term trend reported by different authors are probably due to different approaches used in parameterizing solar activity effects.…”
Section: Long-term Variationmentioning
confidence: 99%
“…Recent comparisons of observed trends with the simulations carried out by Cnossen & Richmond (2013) indicate that magnetic field changes could be responsible for most of the trends in Sq amplitude at three out of five of the stations that were investigated (De Haro Barbas et al 2013), while they could only explain about 8% of the observed trend in ion temperature at Millstone Hill (Zhang & Holt 2013). It still remains unclear whether the increase in CO 2 concentration could be responsible for the remainder, although this seems unlikely based on the results shown here.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, such long-term variation of the Sq amplitude could not be detected near the South Atlantic anomaly region because of the small number of geomagnetic stations distributed in this region. De Haro Barbas et al (2013) also showed that small negative variation of the Sq amplitude can be seen in Europe, India, the eastern part of America, and the southern part of China. The value of the negative Sq trend was ranged from −0.1 to 0.0 nT/year.…”
Section: Global Distribution Of Long-term Variation In the Residual Smentioning
confidence: 92%
“…They explained more than 50% of their trend values with the secular variation in the ambient magnetic field and less than 10% with the increase in greenhouse gases. Recently, De Haro Barbas et al (2013) performed a comparison between the observed and simulated trends in the Sq amplitude at six geomagnetic stations during 1960 to 2000 using Coupled MagnetosphereIonosphere-Thermosphere (CMIT) simulations. They found that the trends in the observed Sq amplitude are in good agreement with the trends expected from the secular variation in the Earth's main magnetic field.…”
Section: Introductionmentioning
confidence: 99%